The associations between proprotein convertase subtilisin/kexin type 9 E670G polymorphism and the risk of coronary artery disease and serum lipid levels: a meta-analysis. Issue 1 (December 2015) - Cai, Gaojun; Zhang, Bifeng; Shi, Ganwei; Weng, Weijin; Ma, Chunyan; Song, Yanbin; Zhang, Ji
Abstract Background Studies had investigated the associations between proprotein convertase subtilisin/kexin type 9 (PCSK9 ) E670G polymorphism and coronary artery disease (CAD) and lipid levels, but the results were controversial. Thus, we performed this meta-analysis to investigate the association betweenPCSK9 E670G polymorphism and lipid levels and the susceptibility to CAD. Methods All relevant articles according to the inclusion criteria were retrieved and included in the present meta-analysis. Odds ratios (ORs) with 95 % confidence interval (CI) were used to analyze the strength of the association betweenPCSK9 E670G polymorphism and the susceptibility to CAD. At the same time, the pooled standardized mean difference (SMD) with 95 % CI was used for the meta-analysis ofPCSK9 E670G polymorphism and lipid levels. The publication bias was examined by using Begg's funnel plots and Egger's test. Results A total of seventeen studies met the inclusion criteria. For CAD association, the pooled effects indicated that the G allele carriers had higher risk of CAD than non-carriers in dominant genetic model (OR:1.601, 95 % CI: 1.314–1.951, P  < 0.001), as well as in allelic genetic model (OR: 1.546, 95 % CI: 1.301–1.838, P  < 0.001). When the subgroup analysis stratified by ethnicity and HWE was performed, the positive result existed in most of the subgroups. For lipid levels association, the pooled effects indicated that the G allele carriers had higher TC and LDL-C levels than the non-carriers (for TC, SMD: 0.126, 95 % CI: 0.023–0.229, P  = 0.016; for LDL-C, SMD: 0.170, 95 % CI: 0.053–0.287, P  = 0.004, respectively). There was no difference in the levels of TG and HDL-C between the G carriers and the non-carriers in the whole population (SMD: 0.031, 95 % CI: −0.048–0.110, P  = 0.440; SMD: −0.123, 95 % CI: −0.251–0.006, P  = 0.061, respectively). When the studies were stratified by ethnicity and type of study, the G carriers had higher TC levels than the non-carriers (SMD: 0.126, 95 % CI: 0.014–0.238, P  = 0.027) in the non-Asian subgroup. The similar results existed in cohort subgroup. The association betweenPCSK9 E670G polymorphism and LDL-C levels was significant in all subgroups. Meanwhile, the G carriers had higher TG levels than the non-carriers (SMD: 0.113, 95 % CI: 0.012–0.214, P  = 0.028) in the case–control subgroup. AG + GG genotypes had lower HDL-C levels than AA genotype in Asian subgroup (SMD: −0.224, 95 % CI: −0.423– −0.025, P  = 0.027) and in case–control subgroup (SMD: −0.257, 95 % CI: −0.467–−0.048, P  = 0.016). Conclusions The present meta-analysis concluded thatPCSK9 E670G polymorphism was associated with CAD risk and lipid levels.